DETECTION AND SEQUENCING GENES IRON, IUTA, AND HLYF IN AVIAN PATHOGENIC ESCHERICIA COLI - Ramaditya, Nyoman Anandiya; Besung, I Nengah Kerta; Mahardika, I Gusti Ngurah Kade (Buletin Veteriner Udayana; Vol. 11 No. 2 Agustus 2019, 2019)
Research has been carried out to detect pathogenic gene markers of Avian Pathogenic Eschericia coli (APEC) iroN , iutA , and hlyF in Escherichia coli bacteria isolated from organs of sick chickens in Bali, and to determine phylogenetic relationships between those marker genes in Bali and in the other countries in the world. Six isolates of E . coli bacteria with codes E2, E3, E7, E8, E9, and E10 were used in this study. The isolates were isolated from domestic chicken in 2018. All genes were detected using the Polymerase Chain Reaction (PCR) method. The genes of iroN , iutA , and hlyF could be detected from all isolates. Well readable sequence of iroN, hlyF, and iutA was 659 bp, 518 bp, and 250 bp, respectively. All three genes were homogenous. Phylogical analysis shows that all pathogenic markers share same cluster with the pathogenic E . coli from all countries in the world.